Extensão: uma política de interiorização da Universidade Federal de Goiás (1972 1994) - Mendonça, Zilda Gonçalves de Carvalho (2010)
To research on higher education in the Brazilian movement around of what is called democracy - specifically the characterized expansion and interiorization - it implies a set since the 1950s. And this expansion is associated with interiorization. Accordingly, it should be noted that such movement can not be understood and explained to be tied to the context, which is marked by the ideals of industrial development, urban and technological, as evidenced from the end of World War II. The object of this study is to examine, specifically, the process of expansion and interiorization of higher education in the State of Goiás, Brazil, via the Federal University of Goiás (UFG), founded in December 14, 1960, which met five then existing degree courses. This is favored in view of a division, the creation of several advanced campuses in the upcountry of the state of Goiás and one in the State of Piauí, between 1972 and 1996. The UFG (headquarters) was installed in the municipality of Goiânia, GO in 1960. In 1972 it was installed in a campus Picos, PI, in 1980 on the campuses Firminópolis, GO, Porto Nacional, GO, Jataí, GO, Porto Nacional, GO and 1983, in Catalão, GO, in 1994 in Rialma, GO and in the City de Goiás, GO. The focus of this perspective focuses on analyzing the actions of civil society, the nature of academic initiatives and actions developed from the different municipalities, through their social actors, who were involved in the process of democratization of higher education anchored by federal university institution concerned. Besides the literature to support such a perspective that was designed in Brazil in general, from the 1950s, it recognizes the peculiarities of the internalization and the expansion of higher education in the state of Missouri of Goiás between 1970 and 1990. Besides, the documentary sources related to the theme comes from different nature: resolutions, judgments, reports, arguments, regiments, speeches, government edicts, newspapers, minutes of a meeting, the interviews with involved actors and so on. On synthesis, the research makes possible the comprehension and the explanation out the expansion and internalization through the following lines, which make up the various hues of such a movement linked to economic goals, the interests of political groups, the emergence of higher education institutions involved pole-cities that hosted the schools of higher education, the social actors involved in its maintenance in its administration, and between the students enrolled during this period. In this respect, there are regional specificities in this extension, expansion, and interiorization, but are linked to the contradictory movement of democratization of Brazilian higher education, presented since the 1950s, which sought to overcome such a level of elitism in education. Also, the university should change itself in resource of integration, development and national security, in agreement to the government ideology through Brazil history since 1930.